The Development Strategies on Batik Creative Industry as an Enthralling Sector for Cultural Tourism in Bondowoso Regency, East Java - Syubbanul Wathon; Kartika Senjarini; Rike Oktarianti (Warta Pengabdian, 2019)
Bondowoso Regency has great potential to evolve into the centers of the batik creative industry. But, there are still no batik products that show the uniqueness of Bondowoso Regency. Several community groups in Suling Wetan Village, Cermee Subdistrict, Bondowoso Regency, have been running a business as batik artisans since 2015. The community groups have had the basic skill to produce batik. Unfortunately, they still don't give any impact on the growth of the cultural tourism destinations in Bondowoso. The old batik designs do not attract buyers, has limited color combinations, and only rely on synthetic batik dyes. Through the partnership service program that have been implemented, some of the Batik community business can develop their products. This partnership service program is done by several activities, such as socialization; workshops on batik design and the use of natural dyes; training on natural materials and batik coloring; procurement of gawangan machines, pendulum and accessories; training and mentoring techniques for making interesting batik motifs and coloring using natural dyes; and the dialogue to develop the creative batik industry. The results of this program are developing not only the Suling Wetan Village but also make the Batik community business in Cermee Subdistrict, independently growth as a creative batik industry. This improvement is also captivating the cultural tourism in Bondowoso Regency.